Growth inhibition in Rhizoetonia bataticola and Xanthomonas axonopodis pv. malvacerum by herbal oils - B T Raut, A R Thakare, S G Wankhade, R B Somani (Journal of Spices and Aromatic Crops, 2003)
Oils extracted from six medicinal plants viz., mentha (Mentha arvensis), ocimum (Ocimum sanctum), lemongrass (Cympobogan flexuosus), citronella (Cympobogan winternus), turmeric (Curcuma longa) and palmarosa (Cympobogan martinii) were tested under in vitro condition for their antifungal and antibacterial properties. Mentha, ocilnum, palmarosa and lemongrass oil exhibited 100% inhibition of Rhizoctonia bataticola at 1 and 2% concentrations, whereas citronella oil recorded 100% inhibition at 2% concentration. Turmeric oil was found to be less effective against Rhizoctonia. Mentha oil showed the highest (17 mm) inhibition zone against Xanthomonas axonopodis pv. malvacerum followed by ocimum oil (12 mm). The studies showed that mentha oil possessed very high inhibitory effects on fungi and bacteria.